2000
DOI: 10.1046/j.1442-2050.2000.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic analysis of lymph node metastasis in surgically resected superficial cancer of the thoracic esophagus

Abstract: We examined lymph node metastasis clinicopathologically in 236 cases of superficial cancer (T1, Tis) of the thoracic esophagus surgically resected at our department without adjuvant treatment. Mucosal cancer was observed in 112 cases (47%) and submucosal cancer in 124 cases (53%). Lymph node metastasis was present in 3% of mucosal cancer cases and 41% of submucosal cancer cases. By the recent pathologic subclassification of the extent of the cancerous invasion in superficial esophageal cancer, mucosal cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(112 citation statements)
references
References 5 publications
10
95
1
4
Order By: Relevance
“…the muscularis mucosa; sm1, tumors invading the most superficial 1/3 of the submucosa; sm2/3, tumors invading deeper than sm1 level) (16,(18)(19)(20)(21)(22). Eguchi et al (21) demonstrated that lymph node metastasis was found in 0, 6, 18, 53 and 54% of m1, m2, m3, sm1 and sm2/3 lesions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…the muscularis mucosa; sm1, tumors invading the most superficial 1/3 of the submucosa; sm2/3, tumors invading deeper than sm1 level) (16,(18)(19)(20)(21)(22). Eguchi et al (21) demonstrated that lymph node metastasis was found in 0, 6, 18, 53 and 54% of m1, m2, m3, sm1 and sm2/3 lesions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This stage is further sub-divided to T1a (also known as T1m and further subdivided to m1: limited to the epithelial layer, m2: invading lamina propria and m3: invading into but not through muscularis mucosa) for tumors that invade the lamina propria or muscularis mucosa; and T1b (also known as T1sm and further subdivided into thirds to sm1, sm2 and sm3: deepest one third of the submucosa) for tumors that invade the submucosa [1,13,18]. The depth of invasion predicts the probability of lymph node metastasis, vascular invasion and long-term survival [19]. There has been much debate and controversy regarding the staging modality for early esophageal cancers.…”
Section: Determining the T Stagementioning
confidence: 99%
“…The lymphatic network is developed and widely spread, lymph node (LN) metastases are very common even in the case of superficial cancer not only in the mediastinum but also in the neck and the abdomen. [1][2][3][4][5] Therefore, the prognosis of thoracic esophageal cancer has been improved since the prevalence of the three-field LN dissection. 6,7) The plenty number of stocked data from the patients have proved the accurate percentage of LN metastases and prognosis after surgery, according to the tumor extent.…”
Section: Introductionmentioning
confidence: 99%
“…6,7) The plenty number of stocked data from the patients have proved the accurate percentage of LN metastases and prognosis after surgery, according to the tumor extent. [2][3][4][5]8) Esophageal squamous cell carcinoma (ESSC) is known to be sensitive to chemo-radiotherapy (CRT). Recent improvements of clinical results in CRT also added the choice for treatment.…”
Section: Introductionmentioning
confidence: 99%